Socio‐economic inequalities in mortality in children with congenital heart disease: A systematic review and meta‐analysis. Issue 4 (26th July 2019) - Best, Kate E.; Vieira, Rute; Glinianaia, Svetlana V.; Rankin, Judith
Abstract: Background: The impact of socio‐economic status (SES) on congenital heart disease (CHD)‐related mortality in children is not well established. Objectives: We aimed to systematically review and appraise the existing evidence on the association between SES (including poverty, parental education, health insurance, and income) and mortality among children with CHD. Data sources: Seven electronic databases (Medline, Embase, Scopus, PsycINFO, CINAHL, ProQuest Natural, and Biological Science Collections), reference lists, citations, and key journals were searched. Study selection and data extraction: We included articles reporting original research on the association between SES and mortality in children with CHD if they were full papers published in the English language and regardless of (a) timing of mortality; (b) individual or area‐based measures of SES; (c) CHD subtype; (d) age at ascertainment; (e) study period examined. Screening for eligibility, data extraction, and quality appraisal were performed in duplicate. Synthesis: Meta‐analyses were performed to estimate pooled ORs for in‐hospital mortality according to health insurance status. Results: Of 1388 identified articles, 28 met the inclusion criteria. Increased area‐based poverty was associated with increased odds/risk of postoperative (n = 1), neonatal (n = 1), post‐discharge (n = 1), infant (n = 1), and long‐term mortality (n = 2). Higher parental education was associated with decreased odds/risk of neonatal (n = 1) and infant mortality (n = 5), but not with long‐term mortality (n = 1). A meta‐analysis of four US articles showed increased unadjusted odds of in‐hospital mortality in those with government/public versus private health insurance (OR 1.40, 95% CI 1.24, 1.56). The association between area‐based income and CHD‐related mortality was conflicting, with three of eight articles reporting significant associations. Conclusion: This systematic review provides evidence that children of lower SES are at increased risk of CHD‐related mortality. As these children are over‐represented in the CHD population, interventions targeting socio‐economic inequalities could have a large impact on improving CHD survival.